The dual role of the supreme court as an administrative system and guardian of the constitution - Delloro, Alder K. (2016)
The 1987 Philippine Constitution has bestowed upon the Supreme Court the institutional and moral integrity as both an administrative system and as a bastion of democratic rights. Behind this dual role of the Supreme Court are two competing ideologies of governance: (1) administrative efficiency, which promotes managerialist approaches and bureaucratic values, and (2) pluralist-democracy, which promotes democratic values. The clashing of these principles has become apparent in many issues confronting the Philippine judiciary, including claims of undue judicial interference and unwarranted judicial prerogative. However, these principles need not be in conflict. Drawing from the insights of local and foreign public administration scholars, the article attempts to explain how the Supreme Court can be an effective bureaucracy and platform for democracy.
Keywords: Justice administration; Supreme Court. Philippines; Bureaucracy